Review on Energy-Efficient Model Hybrid Clustering Technique in WSNs - Iyobhebhe, Matthew; Tekanyi, Abdoulie Momodou . S; Abubilal, K. A; Isiaku, Yau; Agbon, E. E; Obi, Elvis; Umar, Abubakar; Ore-ofe, Ajayi; Kwembe, Benjamin Amough; Botson, Botson Ishaya; Eleshin, Ridwan. O; Ashafa, Fatima; et al. (Vokasi Unesa Bulletin of Engineering, Technology and Applied Science, 2026)
This review article explores the advancements in energy-efficient hybrid clustering techniques for Wireless Sensor Networks (WSNs), highlighting their significance in optimizing energy consumption and enhancing network longevity. As WSNs become integral to various applications, efficient energy management is crucial for prolonging node lifespan and ensuring reliable data transmission. We analyze existing models, comparing their effectiveness in minimizing energy usage while maximizing data delivery efficiency. The review article formulate model equation for determines Energy-Efficient hybrid clustering techniques, Energy consumption, Network Life time, and Data Transmission Delivery which enhances network stability, also discusses the challenges faced in the implementation of these techniques, including scalability and network dynamics. By synthesizing current research, this review aims to provide insights into emerging trends and future directions in energy-efficient clustering strategies, offering valuable guidance for researchers and practitioners seeking to improve the sustainability and performance of WSNs.